Phylogeography and Taxonomic Revision of the Pen Shell Atrina pectinata Species Complex in the South China Sea - Xue, Dong-Xiu; Wang, Hai-Yan; Zhang, Tao (Frontiers in Marine Science, 2021)
Phylogeographic studies contribute to addressing questions regarding the geographic patterns and evolutionary scenarios within and among species and also shed light on the taxonomic status of widely distributed species complexes. The pen shell Atrina pectinata species complex is a widely distributed and economically important bivalve in the northwestern Pacific. Previous phylogeographic studies have identified four genetically distinct cryptic species within the A. pectinata species complex along the coast of China, of which three cryptic species were distributed in the South China Sea. However, less attention has been given to their identification and delimitation. Herein, we report the phylogeography and taxonomic revision of the A. pectinata species complex in the South China Sea using DNA sequence data from mitochondrial cytochrome oxidase I and 16S ribosomal RNA, and nuclear 28S ribosomal RNA markers. Using a combination of phylogenetic and DNA-based species delimitation analysis methods, we found strong support for four genetically valid species in the A. pectinata species complex and defined them as A. japonica, A. lischkeana, Atrina sp. and A. pectinata based on our results as well as on previous morphological and genetic studies. A demographic historical analysis showed that all three species in the South China Sea had populations that were relatively stable over time and then subjected to sudden expansion during the late Pleistocene (60,000-90,000 years ago). These results provide new insights into the systematics and evolution of the A. pectinata species complex and have important conservation and management implications.